2018
DOI: 10.33603/jnpm.v2i2.1291
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Pedagogic Content Knowledge (PCK) Calon Guru Matematika Pada Program Pengalaman Lapangan di SMP/SMA Negeri Kota Cirebon

Abstract: Abstrak. Penelitian ini bertujuan untuk melihat efektifitas instrument PCK yang digunakan untuk menganalisis kemampuan PCK calon guru matematika dan mengetahui perbedaan kemampuan PCK sebelum mengikuti program pengalaman lapangan dengan yang telah mengikuti program pengalaman lapangan. Penelitian ini menggunakan metodedeskriprif kualitatif, dimana mahasiswa tingkat 3G sebagai subjek penelitian.Hasil penelitian menunjukkan (1) kemampuan PCK calon guru matematika kelompok tinggi sudah baik sedangkan kelompok sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Abell (2007) states that the pedagogical content knowledge (PCK) of science teacher candidates influences learning orientation, concept understanding, media use, and scope. They must be accustomed to using instructional media in teaching practices (Aminah & Wahyuni, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Abell (2007) states that the pedagogical content knowledge (PCK) of science teacher candidates influences learning orientation, concept understanding, media use, and scope. They must be accustomed to using instructional media in teaching practices (Aminah & Wahyuni, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Various promoted actions and a variety of teaching depended on the prospective teachers' competence and creativity reflected on their PCK, depending on their academic competence (Aminah & Wahyuni, 2018;Gilang et al, 2019;Maryono, 2016). Subjects or prospective teachers with a PCK level of 0 could still develop their competence by either developing materials or extending the frequency of teaching practice to gain more experience and improve their PCK level (Aminah & Wahyuni, 2018;Jatisunda & Kania, 2020). This study found that the differences in PCK possessed by prospective mathematics teachers can create diversity in the practice of teaching mathematics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important for teacher candidates to adjust the material to Competencies Standard (SK)/KD, time, indicators, and learning objectives in the RPP. Aminah, et al (2018) state one among many factors influencing the success of learning activities is that teachers should possess in-depth insight and understanding towards materials taught. Thus, the teacher candidates with good understanding and proper way to teach will help students to easily understand the materials taught.…”
Section: Goodmentioning
confidence: 99%
“…Thus, the teacher candidates with good understanding and proper way to teach will help students to easily understand the materials taught. Aminah, et al (2018) states that one of the critical success factors in the learning process, where the teacher must have the knowledge and in-depth understanding of the material that will be taught. Thus, prospective teachers who have good knowledge and appropriate teaching methods will help students to more easily build their understanding of the material presented.…”
Section: Goodmentioning
confidence: 99%